Incidence Of Hypoparathyroidism After Total Thyroidectomy for Benign Goitres. A Systematic Review - Ghani, Muhammad Tahir; Haq, Hafiz Muhammad Ijaz ul; Rehman, Ibad Ur; Malik, Huma Azam (Journal of Rawalpindi Medical College, 2023)
Objective: systematic review assessed the overall incidence of hypoparathyroidism after Total thyroidectomy (TT) for benign goitres. Methods: A systematic search of PubMed, google scholar, Cochrane, and Pakmedinet under PRISMA (preferred reporting items for systematic reviews and Meta-analyses) guidelines was performed. All studies during the last 50 years where TT was performed for benign goitres and post-operative hypoparathyroidism was assessed were included. The total incidence of both transient and permanent hypoparathyroidism was calculated after TT for benign goitres. The risk of bias was also assessed. Results: Twelve studies were included in total including eight retrospective, three prospective observational studies, and one randomized trial. Three studies were from Turkey, 2 from Pakistan, 2 from Greece, and one each from Saudi Arabia, India, Denmark, Egypt, and the USA. 2809 TT were performed for benign goitres. Overall Transient hypoparathyroidism (THP) was noted in 290 (10%) patients while permanent hypoparathyroidism (PHP) was noted in 33(1.17%) patients. The highest incidence of permanent hypoparathyroidism was 17% in one study while the lowest was 0% in three studies. The highest incidence of transient hypoparathyroidism was 28.5% in one study while the lowest incidence was 2.5%. The risk of bias was high. Conclusion: TT for benign goitres is associated with 1.17 % overall risk (range 0%-17%) of PHP and 10% (range 2.5%-28.5%) of THP.